29.9k views
5 votes
Solve for w, x, y, z

x + 2y - z = 3
2x - y + z - w = -3
y + 2z - w = -7
x + 3y + 2z + 2w = 3 ​

User JamesKn
by
4.9k points

1 Answer

1 vote

Answer:

x= 1; y= 0; z= -2 and w= 3.

Explanation:

Given that,

1) x + 2y - z = 3

2) 2x - y + z - w = -3

3) y + 2z - w = -7

4) x + 3y + 2z + 2w = 3 ​

now, from 1) z = x + 2y -3 →→(5)

from 2) w = 2x -y + z +3

⇒w = 2x -y + x + 2y -3 +3 (from (5))

w = 3x + y →→(6)

Now substitute (5) and (6) in 3), we get

y +2(x + 2y -3) - (3x + y) = -7

⇒ 4y - x = -1 →→→(7)

Now substitute (5) and (6) in 4), we get

x + 3y + 2(x + 2y -3) + 2(3x + y) = 3

⇒ 9x +9y = 9

⇒ x + y =1 →→→(8)

⇒ x= 1-y , substituting this in (7) gives 5y -1 = -1

y = 0 and x = 1

substituting these values in

(5) and (6) gives, z = -2 and w = 3

⇒ x= 1; y= 0; z= -2 and w= 3.

User Chris Peterson
by
4.6k points